Pengaruh Putusan Mahkamah Konstitusi Nomor 33/PUU-XIII/2015 Dikaitkan dengan Pembatasan Politik Dinasti pada Pemilihan Kepala Daerah - Surya Dewi, Septya Hanung; Riwanto, Agus (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTThis thesis  examines and describes effect of The Constitutional Court Decision Verdict No. 33/PUU-XIII/2015 concerning the restiction of political dynasty on regional chief election and whether the verdict has been appreciate with Constitution of Indonesia, UUD NRI 1945.This research is normative legal research which is descriptive. The result of this research shows that 1) the effect after constitonal court verdict No. 33/PUU-XIII/2015 resulted in article 7 letter r of Law Number 8 of 2015 having no binding legal force and having an impact of implementing regulating under it, as well as creating a conflict of interest. The implemention of regional chief election if there is a conflict of interest resulting in unequal competition, affect the accountability of local elections, political dynasty, and political corruption.However, if there are no conflict of interest, the implementation of local election run smoothly with a strict supervison of all instrumen. 2) the constitutional court verdict No. 33/PUU-XIII/2015  is not according with mandate of Constitution of Indonesia, UUD NRI 1945 Article 28J paragraph (2) and Article 18 paragraph (4)are related to improving the quality of democracy in regional elections.Keywords : constitional court verdict No. 33/PUU-XIII/2015; political dynasty; local election; local election.